(untitled) (Research, Society and Development, 2025)
The article discusses the use of Digital Information and Communication Technologies (DICTs) in the Brazilian educational system, especially regarding the teaching-learning process, aiming to integrate content, skills, and curricular abilities in which the teacher’s role is to incorporate technologies, adapting them to teaching practice with the goal of developing innovative methods. Objective: to address the importance of using DICTs with applicability to curriculum content for the development of teaching and learning. Methodology: The study uses the descriptive method, followed by documentary research of indirect sources in scientific articles in a quantitative study regarding the number of 21 (twenty-one) articles selected to compose the research ’corpus’ and a qualitative nature in the analysis and discussion of the selected articles. Results: 21 publications analyzed in the databases were selected. Final considerations: It is necessary to expand the use of ICTs, increasing interactions between teachers and students through didactic-pedagogical innovations and transformative curricular practices.